Genetic Risk Variants Contributing to Arterial Calcification - Soheili, Fariborz (Université d'Ottawa / University of Ottawa, 2025)
Background: Arterial calcification, characterized by the accumulation of calcium minerals in the arterial wall, is a complex process that is influenced by genetic and molecular factors. This study explores how the 9p21.3 genetic risk variants interact with statherin (STATH), matrix GLA protein (MGP), and the bisphosphonate drug alendronate to affect arterial calcification. Results: Microarray gene expression profiling of human aortic smooth muscle cells (SMCs) revealed that STATH expression was silenced in carriers homozygous for 9p21.3 risk variants. STATH, like MGP, is a hydroxyapatite-binding protein produced by human SMCs that blocks bone morphogenetic protein 4 (BMP4)-dependent signaling, promotes the chondrogenic/osteogenic differentiation, and prevents SMC calcification. In mice lacking MGP (MgpKO), severe arterial calcification leads to death through aortic rupture. However, the expression of human statherin in the SMCs of Mgp-null mice rescued the arterial calcification phenotype. To further investigate the role of MGP and potential treatments, alendronate was tested in mice lacking Mgp (MgpKO mice). Unexpectedly, although alendronate treatment improved dental malocclusion, it also worsened calcification and decreased the number of CD68-positive macrophages in the arterial wall. A single dose of alendronate increased the aberrant expression of the chondrogenic/osteogenic factor Runx2 in SMCs of the aorta of MgpKO mice and alendronate treatment increased calcium endo/lysosomal accumulation in the cultured macrophages. In mouse models, warfarin rapidly induces significant arterial calcification by inhibiting the vitamin K cycle, which prevents the γ-carboxylation of MGP, rendering it inactive. Humans with MGP mutations (Keutel syndrome) show a more variable and milder calcification phenotype than do mice. This difference is partially attributed to the expression of statherin, a hydroxyapatite-binding protein absents in mice but present in human SMCs. Statherin compensates for the loss of MGP in humans and prevents severe arterial calcifications. The 9p21.3 genetic risk variants suppress statherin expression through ALU interaction, which blocks bone morphogenic protein 4 (BMP4)-dependent signaling and prevents calcification in human SMCs, contributing to the variability in arterial calcification observed in individuals with these risk alleles. The paradoxical effects of alendronate in worsening arterial calcification in MgpKO mice suggest that functional MGP is necessary to prevent soft tissue calcification. These findings highlight the complex interplay between genetics, protein expression, and pharmacological interventions, offering new targets for reducing calcification in susceptible individuals.
Keywords: Coronary Artery Calcification; 9p21.3; MGP; Statherin